2019
DOI: 10.18174/466861
|View full text |Cite
|
Sign up to set email alerts
|

Desktop study on autecology and productivity of European lobster (Homarus gammarus, L) in offshore wind farms

Abstract: The Management of Wageningen Marine Research is not responsible for resulting damage, as well as for damage resulting from the application of results or research obtained by Wageningen Marine Research, its clients or any claims related to the application of information found within its research. This report has been made on the request of the client and is wholly the client's property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(59 citation statements)
references
References 31 publications
0
52
0
7
Order By: Relevance
“…Enhancement strategies in OWF's such as food and habitat provision have been assessed for commercial species such as the European lobster (Rozemeijer & van de Wolfshaar, 2019). This desk study concluded that all enhancement strategies (habitat, stock and food) have potential.…”
Section: Landings and Stock Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhancement strategies in OWF's such as food and habitat provision have been assessed for commercial species such as the European lobster (Rozemeijer & van de Wolfshaar, 2019). This desk study concluded that all enhancement strategies (habitat, stock and food) have potential.…”
Section: Landings and Stock Assessmentmentioning
confidence: 99%
“…A DEB model on lobster production in OWF shows that 1 lobster per monopile can reach marketable size (85 mm carapace length (CL) in Dutch waters ) after 3 years when stocked at a length of 50 mm carapace length (Rozemeijer & van de Wolfshaar, 2019). Without restocking it takes about 6 years for lobsters to reach 87 mm CL.…”
Section: Growth Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zo kan het habitat verbeterd worden door het toevoegen van hard substraat (i.e. reefballs), kan er voedsel worden toegevoegd of kunnen jonge individuen worden toegevoegd aan de populatie(Rozemeijer & van de Wolfshaar, 2019). In deze studie is tevens een model gecreëerd die de groei van Europese zeekreeft en de productie simuleert.…”
unclassified
“…Rozemeijer & Van de Wolfshaar (2019) hebben een literatuuroverzicht gemaakt van bekende dichtheden van de Europese zeekreeft. In de Oosterschelde worden dichtheden van 0.0037 individuen per m 2 (berekend voor gehele Oosterschelde) en 0.06 individuen per m 2 (berekend voor dijken) genoemd.…”
unclassified